Economic Specification of Cost Estimates in Dental Programs - Doherty, N.J.G.; Crakes, G.M. (Journal of Dental Research, 1985)
This paper compares two approaches to the estimation of costs in dental care programs: a conventional approach and an approach based on theoretical expectations. The conventional approach typically uses a linear extrapolation of an average figure - e.g., cost per visit - over various program sizes and thus predicts constant costs. Constant costs are, however, theoretically implausible, and it should be anticipated that their use in program planning or analysis would generate biased estimates. This hypothesis is examined using annual costs and visits from a group of uniform clinics over a five-year period. Results show that costs calculated by the conventional method are underestimated at low volumes and increasingly overestimated at higher volumes. The findings, which illustrate how inefficiency can inadvertently be incorporated into program design, have implications for cost-effectiveness of dental care delivery in the public sector. © 1985, SAGE Publications. All rights reserved.
2 citations (Crossref) [2023-10-31]
Keywords: Child; Cost-Benefit Analysis; Delivery of Health Care; Dental Care; Dental Clinics; Dental Health Services; Human; cost; dental health; dept.eco; economic aspect; geographic distribution; health program; human; normal human; organization and management; prevention; short survey; therapy; tooth; united states